Pembelajaran Bahasa Arab di Sekolah Indonesia Luar Negeri dengan Model Materi Ajar Berbasis Pendidikan Karakter Multikultural - Nuruddin Nuruddin; Budiaman Budiaman; Andri Ilham; Ahmad Arifin (Institut Agama Islam Negeri Metro, 2022)
The research aimed to make learning the Arabic language in Indonesian Foreign Schools more effective, efficient and enjoyable, as well as to produce Indonesian diaspora students who possess a strong sense of nationalism and respect for diversity by developing teaching material models that are based on multicultural-based character education values. The research was designed using a research and development model and was conducted in two stages: (1) identifying the needs of students and teachers for Arabic teaching materials that contain multicultural-based character education values; (2) creating a model of Arabic teaching materials that incorporate the values of multicultural-based character education in Indonesian Foreign Schools. The study found a need to develop Arabic teaching materials in Indonesian Foreign Schools, particularly in Arab countries. The development of teaching materials is necessary for two aspects: (1) related to Arabic teaching materials that are based on the values of national character education, in line with learning objectives, and contextually relevant to the present time; (2) in terms of character education, by creating teaching materials that contain character education values such as religious values, nationalism, honesty, independence, cooperation, integrity, hard work, and responsibility.